Effects of salinomycin and ethanamizuril on the three microbial communities in vivo and in vitro - Cheng, Xiaolei; Zheng, Haihong; Wang, Chunmei; Wang, Xiaoyang; Fei, Chenzhong; Zhou, Wen; Zhang, Keyu (Frontiers in Microbiology, 2022)
The fate of a drug is not only the process of drug metabolism in vivo and in vitro but also the homeostasis of drug-exposed microbial communities may be disturbed. Anticoccidial drugs are widely used to combat the detrimental effects of protozoan parasites in the poultry industry. Salinomycin and ethanamizuril belong to two different classes of anticoccidial drugs. The effect of salinomycin and ethanamizuril on the microbiota of cecal content, manure compost, and soil remains unknown. Our results showed that although both salinomycin and ethanamizuril treatments suppressed some opportunistic pathogens, they failed to repair the great changes in chicken cecal microbial compositions caused by coccidia infection. Subsequently, the metabolite5 profiling of cecal content by LC-MS/MS analyses confirmed the great impact of coccidia infection on chicken cecum and showed that histidine metabolism may be the main action pathway of salinomycin, and aminoacyl tRNA biosynthesis may be the major regulatory mechanism of ethanamizuril. The microbial community of manure compost showed a mild response to ethanamizuril treatment, but ethanamizuril in soil could promote Actinobacteria reproduction, which may inhibit other taxonomic bacteria. When the soil and manure were exposed to salinomycin, the Proteobacteria abundance of microbial communities showed a significant increase, which suggested that salinomycin may improve the ability of the microbiota to utilize carbon sources. This hypothesis was confirmed by a BIOLOG ECO microplate analysis. In the animal model of coccidia infection, the treatment of salinomycin and ethanamizuril may reconstruct a new equilibrium of the intestinal microbiota. In an in vitro environment, the effect of ethanamizuril on composting and soil microbiota seems to be slight. However, salinomycin has a great impact on the microbial communities of manure composting and soil. In particular, the promoting effect of salinomycin on Proteobacteria phylum should be further concerned. In general, salinomycin and ethanamizuril have diverse effects on various microbial communities.